Demographic Predictors of Dropping Out of Treatment (DOT) in Substance Use Disorder Treatment. (27th May 2021) - Hanauer, Matthew; Sielbeck-Mathes, Kathryn; Banks, Bre; Mitori, Jessica; Reuveny, Adi
Abstract: Background: Researchers have not studied or used novel methods for identifying potential disparities for sexual minorities, those with criminal pasts, and veterans in (DOT). Methods: We used Bayesian logistic regression to identify factors associated with DOT, tested interaction effects, and used machine learning to classify qualitative responses. Findings: With 2, 772 clients from two inpatient clinics in the Southwest United States, we found sexual minorities and females had 52% and 61%, increases and African Americans had 54% decreases in the odds of DOT. Additionally, those with a criminal past and 34.5 and older were less likely to DOT by 5% relative to clients with no prior involvement in the criminal justice system. Conclusions: This study illustrated the disparities for women and sexual minorities in DOT as well as demonstrated novel methodological approaches to addressing previously unanswered questions.